2000
DOI: 10.1021/jm9911581
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Inhibition of Retroviral Integrases by Styrylquinoline Derivatives

Abstract: Styrylquinoline derivatives, known to be potent inhibitors of HIV-1 integrase, have been experimentally tested for their inhibitory effect on the disintegration reaction catalyzed by catalytic cores of HIV-1 and Rous sarcoma virus (RSV) integrases. A modified docking protocol, consisting of coupling a grid search method with full energy minimization, has been specially designed to study the interaction between the inhibitors and the integrases. The inhibitors consist of two moieties that have hydroxyl and/or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…A fluorescence study of SQ in the absence or in the presence of IN was carried out to get experimental support of the existence of IN-SQ complexes. As found previously (Ouali et al, 2000;Zouhiri et al, 2000) and confirmed in this study (see below), the in vitro inhibition properties of SQ derivatives originate in the simultaneous presence of both C7-COOH and C8-OH groups in the quinoline subunit and are less sensitive to modifications at the C3Ј or C4Ј positions. Accordingly, KHD161 and FZ55 are characterized by very similar inhibition properties.…”
Section: Docking Of Khd161 To the Catalytic Core Domain Of Insupporting
confidence: 89%
See 2 more Smart Citations
“…A fluorescence study of SQ in the absence or in the presence of IN was carried out to get experimental support of the existence of IN-SQ complexes. As found previously (Ouali et al, 2000;Zouhiri et al, 2000) and confirmed in this study (see below), the in vitro inhibition properties of SQ derivatives originate in the simultaneous presence of both C7-COOH and C8-OH groups in the quinoline subunit and are less sensitive to modifications at the C3Ј or C4Ј positions. Accordingly, KHD161 and FZ55 are characterized by very similar inhibition properties.…”
Section: Docking Of Khd161 To the Catalytic Core Domain Of Insupporting
confidence: 89%
“…The structure of the drug KHD161 was optimized as described previously (Ouali et al, 2000) and the tautomeric form with the 7-COO Ϫ and 8-OH groups was used. The drug was rotated by 12°increments and for each of these 12,660 orientations, the translations giving the best overlap were stored when the electrostatic drug-target interaction energy was favorable.…”
Section: Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…They corresponded to KH161, KH211, FZ41, FZ149, KH227, FZ123, and FZ55. Their effects on HIV-1 IN have been described previously (5,10,13,20,33,40,41). The two DKAs, a kind gift from Merck, were L-731,988 and L-839,616.…”
Section: Methodsmentioning
confidence: 99%
“…A number of metal chelates, as agent for mediation of strand scission of duplex DNA and as chemotherapeutic agents, have been used as probes of DNA structure in solution (4,5) . In medicine particularly , a new class of drugs have been reported as potent HIV-1 inhibitors (6,7) , protein tyrosine kinase inhibitors (8) , protozoal -retroviral co-infections (9) , anti HIV-1 agent (10) and therapeutic drugs for the inflammatory diseases (11) . Looking to the above important of DNA binding study of ligands and metal complexes (12,13) , the present paper describes mixed ligand synthesis and DNA binding interaction assay of L1 and L2.…”
Section: Introductionmentioning
confidence: 99%